Complement Protein C1q Interacts with DC-SIGN via Its Globular Domain and Thus May Interfere with HIV-1 Transmission - Pednekar, Lina; Pandit, Hrishikesh; Paudyal, Basudev; Kaur, Anuvinder; Al-Mozaini, Maha Ahmed; Kouser, Lubna; Ghebrehiwet, Berhane; Mitchell, Daniel A.; Madan, Taruna; Kishore, Uday (Frontiers in Immunology, 2016)
Dendritic Cells (DCs) are the most potent antigen presenting cells capable of priming naïve T-cells. Its C-type lectin receptor, DC-SIGN, regulates a wide range of immune functions. Along with its role in HIV-1 pathogenesis through complement opsonization of the virus, DC-SIGN has recently emerged as an adaptor for complement protein C1q on the surface of immature DCs via a trimeric complex involving gC1qR, a receptor for the globular domain of C1q. Here, we have examined the nature of interaction between C1q and DC-SIGN in terms of domain localization, and implications of C1q-DC-SIGN-gC1qR complex formation on HIV-1 transmission. We first expressed and purified recombinant extracellular domains of DC-SIGN and its homologue SIGN-R as tetramers comprising of the entire extra cellular domain including the α-helical neck region, and monomers comprising of the carbohydrate recognition domain only. Direct binding studies revealed that both DC-SIGN and SIGN-R were able to bind independently to the recombinant globular head modules ghA, ghB and ghC, with ghB being the preferential binder. C1q appeared to interact with DC-SIGN or SIGN-R in a manner similar to IgG. Mutational analysis using single amino acid substitutions within the globular head modules showed that TyrB175 and LysB136 were critical for the C1q-DC-SIGN/SIGN-R interaction. Competitive studies revealed that gC1qR and ghB shared overlapping binding sites on DC-SIGN, implying that HIV-1 transmission by DCs could be modulated due to the interplay of gC1qR-C1q with DC-SIGN. Since C1q, gC1qR and DC-SIGN can individually bind HIV-1, we examined how C1q and gC1qR modulated HIV-1-DC-SIGN interaction in an infection assay. Here, we report, for the first time, that C1q suppressed DC-SIGN-mediated transfer of HIV-1 to activated PBMCs, although the globular head modules did not. The protective effect of C1q was negated by the addition of gC1qR. In fact, gC1qR enhanced DC-SIGN-mediated HIV-1 transfer, suggesting its role in HIV-1 pathogenesis. Our results highlight the consequences of multiple innate immune pattern recognition molecules forming a complex that can modify their functions in a way which may be advantageous for the pathogen.